A Survey of Job Satisfaction among Staff of Jundishapur Medical Teaching Hospitals in Ahvaz; Based on Herzberg's Two-Factor Model - Elham Amiri; Kosar Heidari; Ali Khezri; Ali Imani; Farzad Faraji-Khiavi (Taṣvīr-i salāmat, 2017)
Background and Objectives: Job satisfaction is the most important factor affecting the performance and productivity of the organization. The purpose of this study was to assess job satisfaction among staff of Jundishapur medical teaching hospitals; based on Herzberg's      two-factor model. Material and Methods: This was a cross-sectional study. The sample size of 147 was calculated. Stratified sampling method was used. The questionnaire used to collect data consisted of demographic characteristics and job satisfaction in a Likert scale. Data were analyzed using descriptive statistics (mean score and standard deviation) and analytical statistics (Parametric test) in SPSS16 software. Results: In survival factors, the highest average belonged to salary subscale with mean score     (3.35 ± 1.05). The other subscales were estimated relatively inappropriate .Regarding motivational factors; all subscales were estimated relatively inappropriate. The recognition subscale showed a significant association with age (P Conclusion: In order to enhance the efficiency of hospital staff, in addition to the domains that prevent staff from quitting their job, it needs to emphasize on their motivation as well.